Ustrój samorządu terytorialnego : materiały dydaktyczne - Ostapski, Adam; Lisowski, Piotr; Korczak, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The manual is the result of the teamwork of present and former employees of The Institute of Administrative Studies of The Faculty of Law, Administration and Economics of The University of Wrocław. It is a continuation of the previous publications on the system of territorial self-government entities. It was preceded by the collective works: Studies on Territorial Self-Government (edited by Adam Błaś, Kolonia Ltd 2001) and District (edited by Jan Boć, Kolonia Ltd 2000, , which focused on doctrinal considerations. In contrast to these publications, the academic manuals issued since 2006 have been prepared by the team of Authors and are primarily intended as course materials for the purposes of seminars, class discussions and lectures.
Keywords: the supervision of the activities of territorial self-government entities; territorial self-government entities; public administration; district; administrative law; self-government organizational entities; commune auxiliary entities; self-government; province; decentralization; the associations of territorial self-government entities; structural law; Commune